Inklusi Pendidikan Islam: Mewujudkan Pendidikan Semua Anak dalam Konteks Multikultural - Yusuf, M. (Mulya Literasi Publishing, 2023)
The inclusion of Islamic education is an important effort in realizing education that embraces all children, including children with special needs, in an increasingly complex multicultural context. The purpose of this study is to describe the concept of inclusion in Islamic education in a multicultural context, analyze the challenges faced in its implementation, and present effective strategies and practices for achieving inclusion in Islamic education. The research method used is literature analysis and case studies from various Islamic educational institutions that have implemented educational inclusion. The results of the study show that the inclusion of Islamic education is based on the principles of equality, fairness, and recognition of cultural diversity and identity. However, challenges to realizing inclusion in Islamic education include stereotypes and prejudice, limited resources, and a curriculum that does not accommodate the needs of children of diverse backgrounds. To overcome these challenges, effective Islamic education inclusion strategies and practices involve the active participation of parents and the community, an inclusive learning approach, as well as teacher training and development in implementing inclusion. Case studies of implementing inclusive Islamic education demonstrate experiences, challenges, and successes in implementing an inclusive approach. This study concludes that the inclusion of Islamic education in a multicultural context is an important component in creating an education that is just, inclusive, and competitive. Recommendations focus on the need for government support, curriculum renewal, and the active involvement of all parties in realizing Islamic education inclusion. Thus, Islamic education can be a vehicle that embraces all children, builds tolerance, and respects diversity in a multicultural society.